Pengelolaan Sampah Kelapa sebagai Penunjang Ekonomi Hijau Berkelanjutan di Desa Nelayan Kondang Merak, Kabupaten Malang - Fahreza Okta Setyawan; Defri Yona; Sunardi Sunardi; Anatasya Alya Ariyanti; Chiara Dewi Nathania El Zam (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Kondangmerak Beach, Malang Regency, is a tourism and culinary destination, yet it suffers from accumulating young coconut shells that are littered or openly burned, degrading cleanliness and generating pollution and health risks. This community engagement program aimed to establish a circular-economy system that converts coconut-shell waste into charcoal as an alternative fuel for fishery-product processing with the Mina Jaya Mandiri group. We applied a problem–solution-fit approach combining social and technological interventions: hands-on tourism-awareness socialization and workshops, a stainless cart as a designated drop point, and a drum-based dryer with stainless racks powered by used oil. Performance was tracked using operational indicators: kilograms processed, drying time, charcoal substitution rate, and user feedback. Results show improved sorting compliance and a clearer collect–dry–store–use workflow, shorter drying lead time, more stable combustion readiness, reduced shell piles, and better fuel cost efficiency. The program shows appropriate technology and education can strengthen locally sustainable coastal livelihoods.